Mitochondria as Key Players in the Pathogenesis and Treatment of Rheumatoid Arthritis - Clayton, Sally A.; MacDonald, Lucy; Kurowska-Stolarska, Mariola; Clark, Andrew R. (Frontiers in Immunology, 2021)
Mitochondria are major energy-producing organelles that have central roles in cellular metabolism. They also act as important signalling hubs, and their dynamic regulation in response to stress signals helps to dictate the stress response of the cell. Rheumatoid arthritis is an inflammatory and autoimmune disease with high prevalence and complex aetiology. Mitochondrial activity affects differentiation, activation and survival of immune and non-immune cells that contribute to the pathogenesis of this disease. This review outlines what is known about the role of mitochondria in rheumatoid arthritis pathogenesis, and how current and future therapeutic strategies can function through modulation of mitochondrial activity. We also highlight areas of this topic that warrant further study. As producers of energy and of metabolites such as succinate and citrate, mitochondria help to shape the inflammatory phenotype of leukocytes during disease. Mitochondrial components can directly stimulate immune receptors by acting as damage-associated molecular patterns, which could represent an initiating factor for the development of sterile inflammation. Mitochondria are also an important source of intracellular reactive oxygen species, and facilitate the activation of the NLRP3 inflammasome, which produces cytokines linked to disease symptoms in rheumatoid arthritis. The fact that mitochondria contain their own genetic material renders them susceptible to mutation, which can propagate their dysfunction and immunostimulatory potential. Several drugs currently used for the treatment of rheumatoid arthritis regulate mitochondrial function either directly or indirectly. These actions contribute to their immunomodulatory functions, but can also lead to adverse effects. Metabolic and mitochondrial pathways are attractive targets for future anti-rheumatic drugs, however many questions still remain about the precise role of mitochondrial activity in different cell types in rheumatoid arthritis.